The Case for Counsellor Technicians and Counsellor Assistants - Calder, Berry; Tyrrell, Malcolm; Franklyn, Gaston (Canadian Journal of Counselling and Psychotherapy, 2012)
The utilization of two types of paraprofessionals, a coun- sellor technician (CT) and a counsellor assistant (CA), are proposed to overcome the current manpower shortage of professional counsellors in college counselling centres and to alleviate the increasing demand for their services by students, staff, and faculty. The CT will carry out primarily the guidance activities of the college counselling centre, the CA will be involved primarily in the role of "gypsy" counsellor, meeting students informally, such as in the halls and college cafeteria. With the counsellor, they form an efficient, yet flexible team to serve the college population. The relationship between the CA, the CT, and the counsellor is on the level of a small group, a type of social system that is organizationally sound, and singularly suitable for a counselling centre.